AKU manual of clinical practice guidelines / Adil H. Haider (editor in chief) and others. - Haider, Adil H.; Islam, Saleem; Khan, Unab; Sabzwari, Saniya; Khan, Ayesha Habib; Tariq, Muhammad (Karachi : Paramount Books ((Pvt.) Ltd., 2025)
The "AKU Manual of Clinical Practice Guidelines" is a comprehensive, multi-volume reference work published by the Aga Khan University, tailored to the Pakistani healthcare context. It provides evidence-based clinical guidelines for healthcare professionals, addressing the unique medical challenges and practices in the region. -- Volume I: Adult Primary Care focuses on common adult health issues, including cardiovascular diseases, diabetes, respiratory conditions, and infectious diseases, offering guidelines for preventive care and chronic illness management. -- Volume II: Medical Specialties covers specialized fields such as cardiology, endocrinology, gastroenterology, and neurology, providing recommendations for diagnosing and managing complex medical conditions. -- Volume III: Surgery and Surgical Specialties outlines protocols for surgical procedures, perioperative care, and management of surgical complications. -- This manual serves as an essential resource for clinicians, residents, and medical students, promoting standardized, evidence-based practice in Pakistan's healthcare system.
Volume I: Adult primary care -- Volume II: Medical specialities -- Volume III: Surgery and surgical specialities.
Includes bibliographical references and index.
English.
Keywords: Aga Khan University -- Publications; Clinical medicine -- Handbooks, manuals, etc. -- Pakistan; Primary care (Medicine) -- Handbooks, manuals, etc. -- Pakistan; Medical specialties and specialists -- Handbooks, manuals, etc. -- Pakistan; Surgery -- Handbooks, manuals, etc. -- Pakistan; Pakistan -- Handbooks, manuals, etc. -- Health and hygiene